Relationship between radiographic activity on chest computed tomography and microbiological yield in pulmonary tuberculosis cases - Babita,; Suman, Sanjeev; Kumar, Sanjay; Prasad, V. S. (International Journal of Research in Medical Sciences, 2024)
Background: Despite the widespread clinical use of computed tomography (CT), is known regarding the relationship between radiographic activity and microbiological yield in cases of suspected pulmonary tuberculosis (PTB) detected on a CT scan in the chest. Methods: Utilizing data from medical records across multiple centers, we looked at the diagnostic performance for certain PTB. Based on radiographic activity, we divided the patients into four groups: definitely active, possibly active, probably inactive and indeterminate activity. Results: Out of the 162 patients that were included, 79 had PTB that was verified by culture; these patients were categorized into four groups: Undoubtedly active, most likely active, unclear activity, and most likely inactive. These patients made up 48 (29.2%), 81 (49.7%), 17 (10.8%), and 16 (10.3%). In addition to culture rates, TB-PCR and histology data revealed 66.6%, 67.2%, 14.3%, and 0% of each CT radiography procedure respectively, were considered as definitive PTB. Radiography procedure demonstrated good negative predictive values (92.7%, 95% CI, 86.6–96.2) and strong sensitivity (97.1%, 95% confidence interval (CI), 94.6–98.5), which were deemed certainly and probably active PTB in terms of diagnostic efficacy for a certain PTB. According on radiographic activity, respiratory illnesses such non-tuberculous infections caused by mycobacterial and bacterial pneumonia were the most common etiologies other than tuberculosis. Conclusions: Radiographic activity performed well in diagnostics and is readily applicable in therapeutic settings. Nonetheless, physicians must to contemplate alternative options, as radiologic pictures do not validate microbiological patient testing.